Elevated levels of granzyme B correlated with miR-874-3p downregulation in patients with acute myocardial infarction. (September 2017) - Yan, Youyou; Song, Xinjing; Li, Zhibo; Zhang, Jinpu; Ren, Jiajun; Wu, Junduo; Li, Yali; Guan, Yinuo; Wang, Junnan
Aim: Granzyme B could induce apoptosis of target cell in acute myocardial infarction (AMI) and was identified as the target of miR-874-3p by searching the miRNA database. We aim to determine the levels of granzyme B and miR-874-3p as well as assay their correlations or predict powers in AMI.Patients & methods: We measured levels of plasma granzyme B and miR-874-3p in 80 AMI patients or 40 healthy controls and assayed their correlations or predicted powers for AMI.Results: Elevated levels of granzyme B (16.71 ± 7.23 ng/l vs 9.27 ± 3.90 ng/l) correlated with miR-874-3p downregulation (0.20- ± 0.17-fold vs 1.00- ± 0.79-fold) in AMI patients.Conclusion: Plasma miR-874-3p might target granzyme B and it might be an additional biomarker for AMI.